PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH - Rahayuningsih, Sri (FKIP Universitas Wisnuwardhana, 2018)
The purpose of this study was to describe an increase in mathematical communication skills through a problem-based learning model. The method used in this study is descriptive qualitative with the type of research used is tangent circle class material action research. The subjects in this study were class VIII MTs. In this study, students were given a posttest question in the form of a description question which numbered 5 questions in the learning process that used a problem-based learning model. From the results obtained, it will be seen how the mathematical communication skills of MTs students. The results of the study showed that applying the problem-based learning model, students' mathematical communication skills improved.Keywords: mathematical communication, problem-based learning